PREDIKSI UMUR WADUK PANGLIMA JENDRAL BESAR SUDIRMAN BERDASAKAN HASIL PENGUKURAN ECHO-SOUNDING - Darmono Darmono (Universitas Negeri Yogyakarta, 2005)
ABSTRACTThe echo sounding measurement is a method that can be used to know thechange of dam volume directly on the field. This research aims to: (1) know therest of the economic age of the Panglima Besar Jendral Sudirman (PBJS) Dambased on measurement and calculation the echo sounding data, and (2)give more detail view of the changes of the PBJS Dam condition viewed fromsedimentation problem.The research activities were conducted in the PBJS Dam located onKabupaten Banjarnegara, Jawa Tengah. The research utilized secondary datacollected using documentation technique, consists of: (1) sediment volume/year,(2) dam effective volume, (3) dam volume, and total sediment volume year/year. The data were the best mathematic curve interpretationsupported by the Microsoft Excel software. The mathematic curve is indicatedby the variance value coefficient (R) value fromthe various existing trend curve alternatives.The research results show that based on various mathematic curves beingused, since 1999 the rest of operation age of the PBJS Dam lies between 17.37to 20.71 years. This conclusion is a simple prediction without considering thefuture erosion control changes. The rest of the dam age assumps thatthe natural condition especially the sedimentation rate occuring in the dam doesnot change significantly compared to what happened on the previous years andit is not affected by the existing sand mining on the upstream of the dam.Keywords: dam age, echo sounding